2017
DOI: 10.1007/s00455-017-9793-3
|View full text |Cite
|
Sign up to set email alerts
|

Residual Recurrent Nerve Paralysis After Esophagectomy is Associated with Preoperative Lower Serum Albumin

Abstract: Esophagectomy for esophageal cancer is invasive thoracic surgery with a high incidence rate of postoperative complications and prolongation of hospitalization, even if the standardized clinical pathway improves the outcome (mortality and morbidity). Postoperative recurrent nerve paralysis (RNP) is related to respiratory complications concomitant with prolonged hospitalization. However, it has not been elucidated which factors affect the incidence and recovery of RNP. To detect the predictive factor for postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The present results also showed that 1.5% ( n = 2) of the patients continued to receive tube feeding alone 6 months after esophagectomy. Pharyngeal dysphagia and recurrent nerve paralysis were reported to persist 6 months after surgery in some patients with esophageal cancer [ 37 , 38 ]. It is therefore necessary to assess swallowing function and nutritional status sequentially after discharge and provide appropriate swallowing training accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The present results also showed that 1.5% ( n = 2) of the patients continued to receive tube feeding alone 6 months after esophagectomy. Pharyngeal dysphagia and recurrent nerve paralysis were reported to persist 6 months after surgery in some patients with esophageal cancer [ 37 , 38 ]. It is therefore necessary to assess swallowing function and nutritional status sequentially after discharge and provide appropriate swallowing training accordingly.…”
Section: Discussionmentioning
confidence: 99%